Macromorphological Studies on the Extrahepatic Biliary Apparatus in Guinea Fowl (Numida meleagris) - Purushottam, Purushottam (Indian Journal of Veterinary Anatomy, 2020)
The gross anatomical studies on extrahepatic biliary apparatus were performed in 12 Guinea Fowl (Numida meleagris) birds. The most extrahepatic biliary tract components were positioned along with the hepato-duodenal ligament. The right and left hepatic duct has shown their initiation from the respective right and left lobe of liver, which united in the portal fissure to form the common hepatic duct. A pear shaped gall bladder was suspended at visceral surface of the liver with initial segment of duodenal loop. Hartmann’s Pouch, a parity structure ofbulging bag is located on the inferior surface of the infundibulum. The cystic and common hepatic ducts were opening at ventral side of the ascending loop of duodenum. The sphincter of Oddi was observed in the form of neuromuscular component located at the terminal end of duodenum, which facilitate the regulation of flow of Common Hepatic Duct and major pancreatic duct. Common bile duct had a course through the head of the pancreas ending in the sphincter of Oddi, as it was penetrated the duodenal wall where it was formed the ampullaof Vater.